Curahan Tenaga Kerja Keluarga Transmigran dan Lokal pada Pemeliharaan Sapi Potong di Kabupaten Konawe Selatan, Sulawesi Tenggara (Family Labor Allocation of the Transmigrant and Local Farmers for Cattle Raising in Konawe Selatan Regency, Sulawesi Tenggara - La Ode Arsad Sani; Krishna Agung Santosa; Nono Ngadiyono (Buletin Peternakan, 2010)
Development of cattle raising, especially in the location of transmigration project has been lack of informationon the profile of labor allocation. Thirty transmigrated and 30 local farmers raised ≥3 years old cattle, had experience at least three years which lived in the stratified 10 districts were drawn simple randomly as respondents. The average of man day for family labor allocations of the transmigrated and local farmers was 262.91 and 188.49, respectively. The time allocations for cattle raising of transmigrated and local farmers were attending the cattle 0.315 man-days (43.67%) and 0.344 man-days (66.46%), respectively, followed by forage cut and carry activity 0.264 man-days (36.59%) and 0.090 man-days (17.35%), and other activities 0.142 man-days (19.74%) and 0.084 man-days (16.19%). The average of time allocation for non cattle raising activity of transmigrated farmer (0.73 man-days) was higher (P<0.01) than that of local farmer (0.65 man-days). 1.446 man-days (48.85%) of transmigrated farmer family labor time and 1.169 man-days (37.35%) of local farmers’ family labor time were allocated.(Key words: Cattle farming, Family labor, Transmigrated farmer, Local farmer)